ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2015-2019 - Imanullah, Wahyu Rachmaditya; Syaichu, Muhamad (Diponegoro Journal of Management, 2023)
ABSTRACT The energy sector is an industry that specifically influences a company’s production increase and generally affects the country’s economy. The addition of energy sector companies from year to year in Indonesia has led to increased competition in the energy sector. The fluctuation of company values for investors serves as a benchmark for investment decisions and for managers as a benchmark for performance achievements. This research aims to analyze the influence of firm size, net profit margin, debt to equity ratio, institutional ownership, and enterprise risk management on company value (price book value). This research utilized the population of energy sector companies listed on the IDX for the period 2015-2019. The sample obtained consisted of 16 energy sector companies listed on the IDX for the period 2015-2019, selected using purposive sampling technique. The data analysis method employed panel data regression analysis with Eviews 13 as the data processing tool. The results of the study indicate that simultaneously, firm size, net profit margin, debt to equity ratio, institutional ownership, and enterprise risk management significantly influence company value (price book value). Partially, net profit margin, debt to equity ratio, and institutional ownership have a positive and significant effect on company value (price book value), while firm size and enterprise risk management do not have a significant impact on company value (price book value).